2015
DOI: 10.1038/srep16688
|View full text |Cite
|
Sign up to set email alerts
|

The human decapping scavenger enzyme DcpS modulates microRNA turnover

Abstract: The decapping scavenger enzyme DcpS is known for its role in hydrolyzing the cap structure following mRNA degradation. Recently, we discovered a new function in miRNA degradation activation for the ortholog of DcpS in C. elegans. Here we show that human DcpS conserves its role in miRNA turnover. In human cells, DcpS is a nucleocytoplasmic shuttling protein that activates miRNA degradation independently of its scavenger decapping activity in the cytoplasmic compartment. We also demonstrate that this new functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…These data suggest either that DAQ-DcpSi do not regulate miRNA levels, or that any changes are too subtle to be detected using RNA-Seq methodology. The latter interpretation appears most likely based on a demonstrable effect of DAQ-DcpSi reported recently [ 24 ].…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…These data suggest either that DAQ-DcpSi do not regulate miRNA levels, or that any changes are too subtle to be detected using RNA-Seq methodology. The latter interpretation appears most likely based on a demonstrable effect of DAQ-DcpSi reported recently [ 24 ].…”
Section: Resultsmentioning
confidence: 71%
“…Some catalytically-inactive DcpS mutants can also promote Xrn1 activity, indicating that this effect is independent of enzyme activity of DcpS [ 31 ]. These observations have now been extended to human cells showing that DcpS regulates miRNA stability and that although this is a non-catalytic activity function of DcpS it is inhibited by DAQ-DcpSi, possibly due to allosteric modulation of the interaction with XRN2 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCS-1, a decapping scavenger enzyme, interacts with CeXRN1 and promotes the degradation of miRNAs in C. elegans [48]. The human orthologue of DCS-1 is also required for the 5'-3' exoribonuclease function of XRN2 and plays key roles in miRNA degradation [49]. As a marker protein for the 5 -3 mRNA degradation pathway, AtXRN4 has been reported to co-localize with DCP1 in P-bodies [37].…”
Section: Discussionmentioning
confidence: 99%
“…In yeast this is mainly, but probably not exclusively, carried out by a nucleoside diphosphate kinase; in other organisms the enzymes still need to be identified (Taverniti & Séraphin, ). Several other functions of DcpS have been reported: (a) yeast Dcs1 is an obligate cofactor of the 5′→3′ exoribonuclease Xrn1 and facilitates 5′→3′ decay by an unknown mechanism independently of its decapping activity (H. Liu & Kiledjian, ; Sinturel, Bréchemier‐Baey, Kiledjian, Condon, & Bénard, ); (b) the Caenorhabditis elegans DcpS homologue, Dcs‐1 also interacts with Xrn‐1 independently of decapping and degrades specific miRNAs (Bossé et al, ); similar observations were made for human DcpS, which requires Xrn2, the human orthologue of yeast Rat1 (Meziane et al, ); (c) DcpS was also suggested to regulate general mRNA metabolism as its activity influences the amount of cap degradation intermediates, which in turn bind to and recruit cap‐binding proteins (Bail & Kiledjian, ). DcpS may therefore impact upon all cellular events that depend on cap‐binding proteins, including nuclear mRNA processing, nuclear export and translation (Bail & Kiledjian, ; S.‐W.…”
Section: Histidine Triad Proteinsmentioning
confidence: 99%